Future-proof accounting: Data and technology strategies - Akpan, Mfon (U K Emerald Publishing, 2024)
Future-Proof Accounting: Data and Technology Strategies equips accounting students, professors, and industry experts with the knowledge needed to navigate the dynamic realm of accounting.